A chamber study of catalytic oxidation of SO2 by Mn2+/Fe3+ in aerosol water. (15th January 2021) - Zhang, Hailiang; Xu, Yongfu; Jia, Long
Abstract: The catalytic oxidation of SO2 by metal ions in aerosol water may be one of the important sources of sulfate in the atmospheric environment. In order to better understand the catalytic oxidation in aerosol water, a series of experiments were carried out in a smog chamber system under the conditions of relatively low concentrations of SO2 with Mn 2+ /Fe 3+ as catalysts in NaNO3 aerosol water. In the Mn 2+ -catalytic oxidation process, the reaction rate (R) in aerosol water is expressed as R = 2.0 × 10 4 [Mn 2+ ][S(IV)] 1.3 at the initial pH range 4–5, which is about 2 orders of magnitude higher than that in bulk water. When the pH of aerosol water and relative humidity (RH) are high, the catalytic oxidation of SO2 by Mn 2+ in aerosol water is probably an important source of sulfate. In the Fe 3+ -catalytic oxidation process, the reaction rate is significantly lower than that of Mn 2+ -catalytic oxidation, and the rate hardly exceeds 2 orders of magnitude larger than that in bulk water. The role of synergistic catalysis between Fe 3+ and Mn 2+ for oxidation of SO2 in aerosol water is very limited. Highlights: Catalytic oxidation of SO2 with low concentrations by metal ions has been studied in aerosol water. The Mn 2+ -catalytic oxidation rate of SO2 by O2 in aerosol water is 2 orders of magnitude higher than that in bulk water. Fe 3+ and Mn 2+ may only have a small synergistic catalysis in aerosol water, which is not as significant as in bulk water.